Frontier and hot topics in home enteral nutrition based on CiteSpace bibliometric analysis - Qin, Shuwen; Chen, Qin; Huang, Jingjing; Xu, Dandan; Hu, Kangkang; Suo, Yaxi; Hu, Qin; Peng, Yangyao (Frontiers in Nutrition, 2024)
The benefits of home enteral nutrition (HEN) are increasingly recognized, with more scholars focusing on this field. This study aimed to comprehensively identify collaborative networks, analyze, and track research trends, focus on current hotspots, and accurately predict the forefront and focus of home enteral nutrition. Methods: A computer search of the Web of Science Core Collection (WoSCC) was conducted for studies related to home enteral nutrition published from January 1, 2004, to December 31, 2023, and select them in compliance with the PRISMA guidelines. The CiteSpace software was used for bibliometric visualization and comparative analysis of countries, institutions, journals, references, and keywords. Results: A total of 1,113 documents were included, showing a steady annual increase in publication volume. The United States and the Mayo Clinic were the top publishing country and institution, with 302 and 41 papers, respectively. "CLIN NUTR" had the highest number of publications, totaling 221, while "ESPEN guideline on home enteral nutrition" was the most cited reference, with 43 citations. The most prolific author was Manpreet S with 29 papers. Conclusion: The management of HEN is a current research hotspot. The safety of HEN and how to improve patient compliance are critical areas for researchers to consider. Future research could focus on these aspects. The blurring of boundaries between hospital and home care and how to utilize telemedicine technologies to serve more patients deserve in-depth exploration. Researchers worldwide should combine their unique characteristics and advantages to strengthen international cooperation.